Using the 'in-between' to build quality in support relationships with people with cognitive disability: the significance of liminal spaces and time. (2nd January 2023) - Robinson, Sally; Hall, Edward; Fisher, Karen R.; Graham, Anne; Johnson, Kelley; Neale, Kate
ABSTRACT: In a policy context of personalisation, disability support organisations recognise the increasingly contentious nature of clustering people according to disability. Instead, they are placing more emphasis on activities that promote community inclusion. Accordingly, the work between people with cognitive disability and their support workers is increasingly mobile. In this context, drawing on research using a conceptual framework based in recognition theory and social geography, this paper explores how the experience of liminal space-time influenced the working relationships between young people with cognitive disability and their support workers. It found that the pairs used liminal spacetime to build their relationships, creating conditions for mutual recognition to occur, whereby they experienced feeling cared about, respected and valued. These activities and negotiations were mediated at the institutional level by the policies and practices of the disability services. The significance of liminal moments were noted at the interpersonal level, both explicitly and tacitly; but not well taken account of at the institutional level. This disjuncture opens both opportunity and risk to young people and support workers. Appreciating the richness of liminal space-time for identity development opens the way for young people and support workers to use its productive potential.